Assessing the ecological risk to deep-sea megafaunal assemblages from seafloor massive sulfide mining using a functional traits sensitivity approach. (1st September 2021) - Boschen-Rose, Rachel E.; Clark, Malcolm R.; Rowden, Ashley A.; Gardner, Jonathan P.A.
Abstract: The deep sea is subject to multiple anthropogenic disturbances, to which may soon be added mining of hydrothermally-formed seafloor massive sulfides (SMS). As a first step towards a full Ecological Risk Assessment (ERA) for SMS mining, ecological sensitivity to mining activities was assessed based on the functional traits of benthic megafaunal taxa. Faunal distribution and abundance data at two different spatial scales (within seamount and within site) were used from two video surveys conducted at un-fished SMS deposit-hosting seamounts on the Kermadec Volcanic Arc, New Zealand. For each of the 157 taxa identified in the seamount and site surveys, sensitivity was scored for six functional traits: adult size, environmental position, living habit, feeding habit, mobility, and structural fragility. Sensitivity (very low, low, intermediate, high, very high) was scored separately for three mining disturbances: passage of mining vehicles along the seafloor, sediment plumes generated by mining activity, and mineral extraction. The effects of different abundance and diversity weightings on the results were explored and transformations chosen based on ecological rationale. Sensitivity to mining impacts was summed within samples and mapped to show the spatial distribution of sensitivity. Samples (assemblages) consisted of 173 individual 200 m transects for seamount survey data and 153 individual 15 m transects for site survey data. For both spatial scales, the sensitivity of taxa and the sensitivity summed within each sample (assemblage) was greatest to mineral extraction, followed by plume impacts, and least sensitive to vehicle impacts. The location of most very highly sensitive assemblages coincided with the occurrence of hydrothermal vent taxa or previously mapped locations for hydrothermally active habitat. Highly sensitive assemblages occurred at hydrothermally inactive sulfide structures, such as chimneys, and other locations where assemblages were dominated by fragile, sessile, suspension-feeding taxa, such as scleractinian branching corals. The approach taken here illustrates spatial patterns in sensitivity within seamounts and sites and provides an important first step towards a more comprehensive ERA. This type of assessment has the potential to inform decisions on spatial management of SMS mining activities, and the suitable placement of area-based management measures, such as protected areas. Graphical abstract: Image 1 Highlights: Benthic megafaunal distribution and abundance information at two spatial scales were obtained from New Zealand seamounts. Taxonomic and assemblage functional sensitivities were calculated for mineral extraction, plumes, and vehicle impacts. Functional sensitivity was greatest to seabed mineral extraction, followed by plume and then vehicle impacts. The location of very highly sensitive and highly sensitive assemblages coincided with hydrothermally active and inactive habitats. The functional sensitivity approach offers an important first step towards Ecological Risk Assessment.